Quantitative and qualitative initial validation of the accountable talk questionnaire - Kofman Talmy, Ayelet; Mashal, Nira (Frontiers in Communication, 2024)
Accountable Talk (AT) has been extensively studied as a tool for improving argumentation and respectful discourse. While several research tools exist for evaluating AT, as of yet there no self-report assessment tool to measure AT directly, on a large-scale basis, and without significant costs. The aim of the current study was to develop and provide initial validation for a self-report AT questionnaire (ATQ). One hundred students aged 11-12 years participated in the study. Exploratory Factor Analysis was performed. Content validity and test-retest reliability were assessed as well. The results indicated that the questionnaire can reliably assess three separate and independent qualities of AT: accountability to a learning community, accountability to rigorous thinking, and accountability to accurate knowledge.We suggest that the ATQ can be used to evaluate the effectiveness of intervention programs aiming to improve students' acquisition of Accountable Talk skills.